Flood Modelling of Banjir Kanal Barat (Integration of Hydrology Model and GIS) - Marfai, Muhammad Aris (Forum Geografi, 2003)
Hydrological modelling has an advantage on river flood study. Hydrological factors can be easily determined and calculated using hydrological model. HEC-RAS (Hydrological Engineering Centre-River Analysis System) software is well known as hydrological modelling software for flood simulation and encroachment analysis of the floodplain area. For spatial performance and analysis of flood, the integration of the Geographic Information Systems (GIS) and hydrological model is needed. The aims of this research are 1) to perform a flood encroachment using HEC-RAS software, and 2) to generate a flood hazard map. The methodology for this research omprise of 1) generating geometric data as a requirement of the data input on HEC-RAS hydrological model, 2) Hydrological data inputting, 3) generating of the flood encroachment analysis, and 4) transformation of flood encroachment into flood hazard map. The spatial pattern of the flood hazard is illustrated in a map. The result shows that hydrological model as integration with GIS can be used for flood hazard map generation. This method has advantages on the calculation of the hydrological factors of flood and spatial performance of the flood hazard map. For further analysis, the landuse map can be used on the overlay operation with the flood hazard map in order to obtain the impact of the flood on the landuse.